PENGOLAHAN LJMBAH HASIL PERTANIAN DENGAN POKOK PERHATIAN KEPADA LIMBAH KELAPA SAWIT - R Sudradjat; Dedi Hartadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
The experivnent deals with conversion of oil palm shell lo activated carbon, solid state fermentation of oil palm wastes i.e : empty fruit bunch (EFB). pericarp as well as King grass, bagasse, sago waste and cayepus leaves residue. The experiment was conducted also on liquid state fennentation of oil palm process water i. e : waste waler coming from fresh fruit bunch (FFB) sterilization part and mud waste from oil extraction part. The method used for solid and liquid state fermentation were set at about optimum condition process according to the previous experiments.The results showed tluu activated carbon from oil palm shell gave iodine absorption of 950 mg/g and yield of 22 percent by using NaOH as an activatar.For solid stare fermentation , pericarp gave the highes COD degredation (61 %), VS (31. 4 %), CIN ratio (35. 7 %) and cellulose (26 %) the highest biogas produation (0. 211 t/g COD) while bagasse gave the highest lignin degradation (2. 2 %).For liquid state fermentation, The use of PUR as captive material gave the highest COD, SS and VSS degradation either for mud waste and waste water. The highest COD degradation of mud waste was 79%, SS 78%, VSS 79% and biogas production of 3.7 l/g COD.